2006
DOI: 10.1093/aje/kwk009
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Carotenoids and Risk of Colorectal Cancer in a Pooled Analysis of 11 Cohort Studies

Abstract: Dietary carotenoids have been hypothesized to protect against epithelial cancers. The authors analyzed the associations between intakes of specific carotenoids (alpha-carotene, beta-carotene, beta-cryptoxanthin, lutein + zeaxanthin, and lycopene) and risk of colorectal cancer using the primary data from 11 cohort studies carried out in North America and Europe. Carotenoid intakes were estimated from food frequency questionnaires administered at baseline in each study. During 6-20 years of follow-up between 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 65 publications
1
37
1
3
Order By: Relevance
“…For example, in other studies of the participants in the Health Professsionals Follow-up Study, no association was observed between lycopene intake and the risk of oral premalignant lesions [69] or between tomato consumption and the risk of bladder cancer [70]. In a pooled analysis of food frequency questionnaires from 11 cohort studies including more than 700,000 participants and 7,885 incident cases of colorectal cancer, tomato consumption was found to provide no reduction in the risk of colorectal cancer [71].…”
Section: Clinical Trialsmentioning
confidence: 91%
“…For example, in other studies of the participants in the Health Professsionals Follow-up Study, no association was observed between lycopene intake and the risk of oral premalignant lesions [69] or between tomato consumption and the risk of bladder cancer [70]. In a pooled analysis of food frequency questionnaires from 11 cohort studies including more than 700,000 participants and 7,885 incident cases of colorectal cancer, tomato consumption was found to provide no reduction in the risk of colorectal cancer [71].…”
Section: Clinical Trialsmentioning
confidence: 91%
“…6 However, pooled analyses of prospective studies showed no association between dietary intakes of carotenoids or between any of the vitamins A, C or E and CRC risk. 7,8 If an inverse association truly existed, the lack of observed associations may have resulted from measurement errors in dietary questionnaire assessments causing attenuation of risk estimates. 9 Studies examining the association between blood concentrations of carotenoids and vitamins A, C and E with CRC risk have generally been inconclusive as well and have reported only suggestive risk reductions for carotenoids (most notably b-carotene) and vitamins A (retinol) and E (tocopherols).…”
mentioning
confidence: 99%
“…Narisawa et al [135] reported that tomato juice containing lycopene protects against the development of induced colon cancer. A meta-analysis of observational studies indicates the potential role of lycopene in the prevention of colorectal cancer [136]. A case-control epidemiological study of 728 Italian rectal cancer subjects and 1225 colon cancer patients confirmed a 20% reduction in the risk of colorectal cancer by the addition of one daily serving of vegetable (in the form of tomato) [137].…”
Section: Cancermentioning
confidence: 99%